Development Si Ceria Game in Science Subjects in Class VIII SMP - Alfitri, Bilqisti Rohmatun; Bentri, Alwen; Yusri, Meldi Ade Kurnia; Amsal, Mutiara Felicita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Learning media is a tool for teachers to convey information during the learning process. However, many schools still use learning media that are less varied and less engaging, causing students to tend to lose focus during the explanation process in learning. With the presence of technology, it can be used as an engaging learning medium in the form of the cheerful game in the subject of Science. This research aims to produce a valid and practical cheerful game media for the 8th-grade junior high school Science subject. The type of research is development research known as Research and Development (R&D) using the 4D model. The development procedure in this research consists of 4 stages. (Define, Design, Develop, and Disseminate). The product validity test was conducted by 3 validators, namely 1 material validator and 2 media validators. The practicality test was trialed on eighth-grade students of SMP Muhammadiyah 6 Padang. Based on the assessment results from the material and media validators, the material validation obtained an average score of 4.60 with the category